2016
DOI: 10.3390/ijerph13020192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbiological and Chemical Contaminants in Poultry Farms

Abstract: The aim of the study was to evaluate the microbiological and chemical contamination in settled dust at poultry farms. The scope of research included evaluating the contributions of the various granulometric fractions in settled dust samples, assessing microbial contamination using culture methods, concentrations of secondary metabolites in dust and their cytotoxicity against hepatocyte chicken cells by means of MTT (3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide) tests. In addition, we also evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 35 publications
4
65
0
6
Order By: Relevance
“…Само по себе промышленное содержание птицы служит мощным стрессорным фактором, модулирующим реакции врожденного и приобретенного иммунитета, снижающим резистентность птиц даже к собственной микробиоте, что создает предпосылки для воздействия бактерий на организм и быстрого распространения возбудителей болезней. В последние годы в птицеводческих хозяйствах возросла циркуляция условно-патогенных и патогенных микроорганизмов, которые могут быть причиной пищевых отравлений человека (17)(18)(19). Необходимость исследования динамики распространения антибиотикорезистентности у представителей семейства Enterobacteriaceae не вызывает сомнения.…”
unclassified
“…Само по себе промышленное содержание птицы служит мощным стрессорным фактором, модулирующим реакции врожденного и приобретенного иммунитета, снижающим резистентность птиц даже к собственной микробиоте, что создает предпосылки для воздействия бактерий на организм и быстрого распространения возбудителей болезней. В последние годы в птицеводческих хозяйствах возросла циркуляция условно-патогенных и патогенных микроорганизмов, которые могут быть причиной пищевых отравлений человека (17)(18)(19). Необходимость исследования динамики распространения антибиотикорезистентности у представителей семейства Enterobacteriaceae не вызывает сомнения.…”
unclassified
“…On a broader scale, microorganism could be shed via/from activity (coughing, sneezing, talking, or breathing), skin and excrement of individuals and aerosolized into airborne microorganism [41,[58][59][60][61]. Large amount of particulate matter and microorganism, including pathogens, were emitted from animal houses by the ventilation system [62][63][64][65], which resulted in higher concentration of particulate matter and airborne microorganism in their vicinity [66,67]. An airborne transmission model, which obtained from Gaussian Plume Model by incorporating the dust deposition process, pathogen decay, and a model for the infection process on exposed farms, revealed that wind-borne route alone was insufficient when compare transmission risk pattern predicted by the model with the pattern observed during the 2003 epidemic [68].…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia concentration of 20 ppm will cause eye and airway irritation in poultry, resulting in impaired feeding, lower weight gain and larger susceptibility to viral infections, thus being considered a critical level of ammonia (20,21). Carbon dioxide is present in the atmosphere at a concentration of 300-400 ppm, with 3000 ppm as the maximal allowed level in the air of poultry house (11,22). Higher air concentrations of carbon dioxide will cause circulatory derangements and appetite reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Considering microorganisms, saprophytic bacteria prevail in poultry houses; however, the presence of pathogenic bacteria, fungi, spores and other microorganisms has also been reported. Nearly 80% of microorganisms present in the air of poultry houses originate from the animals accommodated there (9)(10)(11). Air concentrations of microorganisms and noxious gases depend, among others, on bird age, type of housing system and stocking density, manure management, efficiency of ventilation, and microclimate that is primarily determined by air temperature, relative humidity and airflow rate.…”
Section: Introductionmentioning
confidence: 99%